Cobalt-doped graphitic carbon nitride with enhanced peroxidase-like activity for wastewater treatment. Issue 42 (12th April 2016) - Mu, Jianshuai; Li, Jie; Zhao, Xin; Yang, En-Cui; Zhao, Xiao-Jun
Abstract : The peroxidase-like activity of graphitic carbon nitride (g-C3 N4 ) is dramatically increased by a small cobalt doping. The cobalt-doped g-C3 N4 was used for wastewater treatment, exhibiting much higher degradation rate than that of pure g-C3 N4 . Abstract : Cobalt-doped graphitic carbon nitride (Co-g-C3 N4 ) materials with different cobalt contents were prepared by a facile one-pot thermal condensation method with urea and cobalt chloride. The morphology and composition of the synthesized products were characterized by different techniques. X-ray photoelectron spectroscopy and elemental mappings revealed that cobalt element is highly dispersed in the framework of g-C3 N4 . For the first time, Co-g-C3 N4 was demonstrated to own dramatically enhanced peroxidase-like activity, compared with pure g-C3 N4 . Its activity is dependent on the content of cobalt doping, and the optimal content is 2.5% (Co-g-C3 N4 -2) based on the result of inductively coupled plasma atomic emission spectroscopy. The catalytic kinetics reveals that Co-g-C3 N4 -2 has a higher affinity for the substrate 3, 3′, 5, 5′-tetramethylbenzidine (TMB) and similarly efficient performance in comparison to that of natural peroxidase. The proposed mechanism demonstrates that cobalt dopant facilitates the electron transfer of Co-g-C3 N4 from TMB to H2 O2, thus enhances its peroxidase-like activity. Based on the greatly enhanced peroxidase-like activity, Co-g-C3 N4 -2 is firstly used for wastewater treatment. With rhodamine B as a model, Co-g-C3 N4 -2 exhibits 11 times higher degradation rate than that of pure g-C3 N4 . This research will be helpful to improve the development of efficient artificial peroxidase mimic for removing contaminants from wastewater.